Dampak Shock Variables terhadap Kinerja Pembiayaan UKM pada Bank Perekonomian Rakyat Syariah (BPRS) di Indonesia - Yaman, Afdhal; Nihaya, Ina Uswatun (BISNIS, 2025)
The purpose of this study is to examine the long-term and short-term relationships between macroeconomic variables, namely the BI rate, inflation, and the exchange rate, and SME financing at Bank Perekonomian Rakyat Syariah (BPRS) in Indonesia. This study employs a quantitative approach using secondary time-series data from April 2016 to April 2025. The analytical method used is the Vector Error Correction Model (VECM), which is a restricted form of the Vector Autoregressive (VAR) model. Before estimating the VECM, several preliminary tests are conducted, including the stationarity test, optimal lag length test, stability test, cointegration test, and Granger causality test. Afterward, the VECM estimation is performed, followed by the impulse response function (IRF) analysis. Based on the results, the BI rate and the exchange rate exhibit varying responses across periods, while inflation consistently shows an increasing response in each period of SME financing. Similarly, the contributions of the BI rate and the exchange rate to SME financing fluctuate over time. In contrast, the contribution of inflation to SME financing at BPRS in Indonesia continues to increase in each period.